Hygiene Sanitasi Pedagang dan Keberadaan Bakteri Escherichia Coli pada Es Buah di Kota Semarang Tahun 2025 - Ana Yustika; Dewi Setya Rini; Sri Ratna Astuti; Seno Ari Tjahjo P; Ana Khoirul Ummah; Prasojo Prasojo (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2025)
Fruit ice is one of the most popular street foods in Semarang City due to its refreshing taste and affordable price. However, improper hygiene and sanitation practices during preparation may lead to contamination by pathogenic microorganisms, including Escherichia coli as an indicator of fecal contamination. This study aims to describe the hygiene and sanitation practices of fruit ice vendors and to identify the presence of Escherichia coli in the products sold in Semarang City. This research applied a descriptive quantitative method with a comparative design. The population consisted of all fruit ice vendors in Semarang City, with a total of 30 vendors selected using total sampling technique. Data were collected through observation, interviews, and laboratory examination using MacConkey Agar medium. The results showed that most vendors did not meet hygiene and sanitation requirements, and out of 30 fruit ice samples examined, 20 were found positive for Escherichia coli. The study concludes that hygiene and sanitation practices among fruit ice vendors in Semarang City remain inadequate, and the presence of Escherichia coli in the products indicates potential public health risks. It is recommended that continuous training for vendors, regular supervision by health authorities, and community education be conducted to encourage consumers to select safer food options.